Semen characteristics and refrigeration in free-ranging giant anteaters (Myrmecophaga tridactyla) - Luba, Camila do Nascimento [UNESP]; Boakari, Yatta Linhares [UNESP]; Lopes, Alexandre Martins Costa; Gomes, Marcelo da Silva; Miranda, Flávia Regina; Papa, Frederico Ozanan [UNESP]; Ferreira, João Carlos Pinheiro [UNESP] (Elsevier B. V., 2015)
The giant anteater (Myrmecophaga tridactyla) is considered vulnerable to extinction. Scientific data on the reproductive parameters of this species are scarce. Semen from eight free-ranging giant anteaters was collected to establish its characteristics and the effects of cooling and storage at 5 °C after dilution with the BotuCrio extender without cryoprotectant. The ejaculate presented two distinct sequential fractions, including a whitish fraction, which was milky and rich in sperm cells, and a gel fraction, which was colorless, viscous, and azoospermic. The mean ± standard error of the mean values of the seminal characteristics were as follows: volume of the first fraction, 0.75 ± 0.1 mL; motility, 75 ± 2.9%; vigor, 3.2 ± 0.3; sperm motility index, 68.8 ± 4.3; concentration, 108.5 ± 13.4 × 10(6)/mL; plasma membrane integrity index, 71 ± 4.0%; spermatic defects detected using modified Karras staining, 35.5 ± 3.3%; and spermatic alterations identified by differential interference contrast microscopy, 48.3 ± 6.8%. During refrigeration, the semen presented decreasing motility from 0 to 18 hours, sperm motility index decreased from 0 to 24 hours, and vigor did not change in the first 6 hours and then decreased to 18 hours.
Keywords: Electroejaculation; In situ; Myrmecophagidae; Pilosa; Reproduction; Xenarthra